Propensity score-based comparison of high-risk coronary artery bypass grafting vs. left ventricular assist device implantation in patients with coronary artery disease and advanced heart failure - Nersesian, Gaik; Abd El Al, Alaa; Schoenrath, Felix; Zittermann, Armin; Hell, Laurenz; Falk, Volkmar; de By, Theo M. M. H.; Fox, Henrik; Schramm, Rene; Morshuis, Michiel; Gummert, Jan; Potapov, Evgenij; et al. (Frontiers in Cardiovascular Medicine, 2024)
Revascularization in patients with severely reduced left ventricular function and coronary artery disease (CAD) is associated with a high perioperative risk. In this setting, implantation of a durable left ventricular assist device (LVAD) might be an alternative.We retrospectively compared the outcomes of adult patients with CAD and a left ventricular ejection fraction (LVEF) ≤25% who underwent coronary artery bypass grafting (CABG) vs. LVAD implantation. Propensity score (PS) matching was performed for statistical analysis, resulting in 168 pairs.In the PS-matched cohorts, the mean age was 62 years; one third had a history of myocardial infarction, 11% were resuscitated, half of the patients were on inotropic support, and 20% received preoperative mechanical circulatory support.LVAD patients required significantly longer ventilation (58h [21, 256] vs. 16h [9, 73], p<0.001) and had a longer ICU stay (11d [7, 24] vs. 4d [2, 10], p=<0.001) compared to CABG patients The incidence of postoperative renal replacement therapy (2 [1.2%] vs.15 [8.9%], p=0.002) and temporary mechanical circulatory support was lower in the LVAD group (1 [0.6%] vs. 51 [30.4%], p=<0.001). The in-hospital stroke rate was similar (LVAD 7 [5.4%] vs. CABG 8 [6.2%], p=0.9).In-hospital survival, 1-year survival, and 3-year survival were 90.5% vs. 85.5% (p=0.18), 77.4% vs. 68.9% (p=0.10) and 69.6% vs. 45.9% (p<0.001), for CABG and LVAD patients respectively.Patients with CAD and advanced HF demonstrate better mid-term survival if they undergo CABG rather than LVAD implantation.• va-ECMO -veno-arterial extracorporeal membrane oxygenation• VIS -vasoactive inotropic score• WBC -white blood cell count• CTO -chronic total occlusion